One Suro Night Tradition: Alms Earth and the Dynamics of Its Influence in Community Social and Religious Life - Mulyani, Mulyani; Abdulhassan, Nahidah J.; Noori, Muhammad Ishaq (Jurnal Pendidikan Agama Islam Indonesia (JPAII), 2023)
Purpose of the study: This research aims to find out about the Suro one night tradition, especially the earth almsgiving and its influence on the socio-religious life of the community. Methodology: This research adopts a quantitative approach with a phenomenological focus. In this research, the data collection techniques used involved interview and observation instruments. In detailing the findings from data collection, this research applies Milles and Huberman data analysis techniques. Main Findings: The results of observations show that the Suro first night tradition, especially in the context of earth almsgiving, has a significant impact on the social and religious life of the community. From the results of interviews with participants, it was revealed that the Suro first night tradition, especially the earth almsgiving, has a deep meaning for the community. Novelty/Originality of this study: One Suro Night Tradition, deeply rooted in local culture, serves as a unique catalyst in shaping the social and religious fabric of communities. Its profound influence extends beyond traditional practices, resonating within madrasahs, islamic boarding school, and public schools, fostering a harmonious convergence of cultural heritage and modern education.